2015
DOI: 10.1080/15538605.2015.1029204
|View full text |Cite
|
Sign up to set email alerts
|

Religion, Spirituality, and LGBTQ Identity Integration

Abstract: Processes of navigating intersections between spiritual/religious identity and lesbian, gay, bisexual, transgender, or queer (LGBTQ) identity are just beginning to be explicated. In-depth interviews with 35 LGBTQ adults from a range of backgrounds explore experiences with religion and spirituality. Although not all participants experienced conflicts, the psychological and emotional harms done to some participants through organized religion were extensive and knew no age boundaries. Disconnection from bodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(92 citation statements)
references
References 35 publications
(86 reference statements)
4
78
0
Order By: Relevance
“…Subhi and Geelan (2012) reported that in their study a small percentage of individuals experienced no conflict between sexuality and faith because they either "abandoned" their faith prior to 'coming out' or continued identifying as a Christian but did not practise or attend church. This is consistent with other papers in this review that note individuals' responses around 'separating religion, church and spirituality' (Began & Hattie, 2015) and 'concealment of sexual orientation' (Ho & Hu, 2016). Resolution, for some, required 'compartmentalisation' of their life (Ho & Hu, 2016) or finding a 'new path' (Began & Hattie, 2015) or 'new space' (Ho & Hu, 2016).…”
Section: Resolutionsupporting
confidence: 89%
See 4 more Smart Citations
“…Subhi and Geelan (2012) reported that in their study a small percentage of individuals experienced no conflict between sexuality and faith because they either "abandoned" their faith prior to 'coming out' or continued identifying as a Christian but did not practise or attend church. This is consistent with other papers in this review that note individuals' responses around 'separating religion, church and spirituality' (Began & Hattie, 2015) and 'concealment of sexual orientation' (Ho & Hu, 2016). Resolution, for some, required 'compartmentalisation' of their life (Ho & Hu, 2016) or finding a 'new path' (Began & Hattie, 2015) or 'new space' (Ho & Hu, 2016).…”
Section: Resolutionsupporting
confidence: 89%
“…This is consistent with other papers in this review that note individuals' responses around 'separating religion, church and spirituality' (Began & Hattie, 2015) and 'concealment of sexual orientation' (Ho & Hu, 2016). Resolution, for some, required 'compartmentalisation' of their life (Ho & Hu, 2016) or finding a 'new path' (Began & Hattie, 2015) or 'new space' (Ho & Hu, 2016). For others, an individualised relationship to spirituality is developed (Began & Hattie, 2015).…”
Section: Resolutionsupporting
confidence: 89%
See 3 more Smart Citations